Tinjauan Hukum Islam Terhadap Tradisi Mammanu’-Manu’ - Muhammad Saleh; Jumadil Jumadil; Ilham Ilham (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2022)
The results of the study show that the Mammanu'-manu' tradition is the initial stage in the preparation of a Bugis Makassar traditional wedding. Mammanu'-manu' is an activity carried out by a boy's family to investigate the status of the girl he wants to marry. This activity is to determine whether the girl already has a relationship with another man or not. In addition, it is also ensuring whether the girl is in an equivalent quality with the man. Usually mammanu'-manu' is represented by women from male families who are considered capable of doing this. In the process, mammanu’-manu’ certainly has two possibilities which are important aspects of whether or not a marriage is implemented. And it has become a mutual agreement depending on the result of the mammanu’-manu’ themselves. Mammanu’-manu’ in Islamic law includes in the need for tahsiniyah, the need for tahsiniyah means the human need for things that are considered commendable in the customs of their daily life and stay away from an unfavorable atmosphere